In Vitro Biofilm Formation and Antibiotic Susceptibility Patterns of Bacteria from Suspected External Eye Infected Patients Attending Ophthalmology Clinic, Southwest Ethiopia - Kuma Diriba; Tesfaye Kassa; Yared Alemu; Sisay Bekele (International Journal of Microbiology)
Background. Ocular disease with its complications is a major public health problem which has significant impacts on the quality of life particularly in developing countries. An eye infection due to bacterial agents can lead to reduced vision and blindness. This study was aimed to assess the antimicrobial susceptibility pattern and biofilm-forming potential of bacteria isolated from suspected external eye infected patients in Jimma. Method. A cross-sectional facility-based study was conducted on 319 suspect patients with external eye infections from March to June 2017 at Jimma University Medical Center (JUMC) Ophthalmology Department in Ethiopia. External ocular specimens were collected and standard operating procedures were followed to handle and culture throughout the study period. Antimicrobial susceptibility was determined by the disk diffusion method according to CLSI guidelines. Microtiter (96 wells) plate method was used to screen biofilm formation by ELISA reader at 570 nm. Results. Out of 319 study participants with an external eye infection, the prevalence of bacterial pathogens was 46.1%. The predominant bacterial isolates were coagulase-negative staphylococcus (CoNS) (27.7%) followed by Staphylococcus aureus (19.7%). Among Gram-negative groups, Pseudomonas aeruginosa (6.8%) was the leading isolate. Increased antimicrobial resistance was observed for tetracycline (64%), erythromycin (66.7%), and penicillin (77.1%). Amoxicillin-clavulanic acid, ciprofloxacin, and gentamicin were the most effective drugs for external eye infections due to susceptibility ranging from 70 to 100% among both Gram-negative and Gram-positive groups. Methicillin-resistant S. aureus (MRSA) accounted for 13.8%. Multidrug resistance (MDR) accounted for 68.7%. The overall biofilm formation rate of bacterial ocular pathogens was 66.1%, where P. aeruginosa (40%), CoNS (34.1%), and S. aureus (31%) formed strong biofilm phenotype. Conclusion. The prevalence rate of bacterial isolates was high. Almost all bacterial isolates were resistant to at least one or more drugs. MDR pathogens were observed increasingly among biofilm formers or vice versa.